2011
DOI: 10.1007/s10734-011-9410-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of factors influencing research productivity of agriculture faculty members in Iran

Abstract: The purpose of this research is to analyze the relationship between individual, institutional and demographic characteristics on one hand and the research productivity of agriculture faculty members on the other. The statistical population of the research comprises 280 academic staff in agricultural faculties all over Tehran Province. The data regarding research productivity and demographic characteristics were extracted from the faculty members' profiles. Questionnaires were utilized to collect information co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
58
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 21 publications
14
58
1
1
Order By: Relevance
“…Hedjazi and Behravan (2011) also found that financial rewards are more welcomed by faculty members than symbolic ones. Some other researchers note that the most effective combination of financial and non-financial rewards seems to vary for each individual.…”
Section: Rewarding Staffmentioning
confidence: 94%
See 1 more Smart Citation
“…Hedjazi and Behravan (2011) also found that financial rewards are more welcomed by faculty members than symbolic ones. Some other researchers note that the most effective combination of financial and non-financial rewards seems to vary for each individual.…”
Section: Rewarding Staffmentioning
confidence: 94%
“…Non-financial rewards can be in the form of praise and recognition by managers (Santo et al 2009), mention in bulletins, and "lionization" at scientific conferences (Hedjazi and Behravan 2011). Popular forms of financial rewards may be salary bonuses (for instance, market loadings), accelerated promotion, funding for travel, conference attendance, and further research (Taylor 2006).…”
Section: Rewarding Staffmentioning
confidence: 99%
“…The study of Hedjazi and Behravan (2011), based on the model of Bland et al (2005), examined individual, institutional, and demographic characteristics that influenced research productivity among faculty members of an agriculture department in Tehran Province. The results indicate that several factors have meaningful relationships with the faculty members' research productivity, including age, academic rank, university of graduation, department type, creativity, self-confidence, working habits, research objectives, corporate management style, counseling system, network of communication with colleagues, research opportunities, experience and skill, researchorientation, and sources of facilities in the organization.…”
Section: Factors Affecting Research Performancementioning
confidence: 99%
“…Studies have shown that personal characteristics such as age, gender, socioeconomic status, family-related factors, educational background/graduate training, industry experience, academic rank, intrinsic academic motivation, among others, have an effect on the research productivity of academic faculty (Bell & Seater, 1978;Braxton & Bayer, 1986;Hedjazi & Behravan, 2011;S. Levin & Stephan, 1989;Lin & Bozeman, 2006;Ramsden, 1994;Sax, Hagedorn, Arredondo, & Dicrisi III, 2002).…”
Section: Determinants Of Academic Research Productivitymentioning
confidence: 99%
“…The work at the level of focuses on the impact of institutional factors (for example, Davenport et al, 2002); the role played by personal factors is largely ignored. The present study fills this gap in the literature by identifying the institutional/structural factors and personal characteristics (Hedjazi & Behravan, 2011;Ramsden, 1994) that contribute to the quantity and quality of research produced by faculty in HTM. The need to measure both the quantity and quality dimensions of knowledge worker productivity (Ramírez & Nembhard, 2004), including faculty researchers (Gonzalez-Brambila & Veloso, 2007), has been highlighted.…”
Section: Introductionmentioning
confidence: 98%